Penyediaan Pakan Ternak Melalui Intervensi Teknologi Alat Pencacah Limbah Cangkang Kepiting Di Desa Puasana Kecamatan Moramo Utara Kabupaten Konawe Selatan - Aksar, Prinob; Hasanudin, La; Samhuddin, Samhuddin; Mangalla, Lukas Kano; Barata, La ode Ahmad; Sudia, Budiman; Saputra, Jaka seru Dwi (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2023)
The aim of the community service activity is to effectively provide technical guidance to the community, especially the farmers in Puasana Village, North Moramo Sub-district, on the creation, operation, and maintenance of the Crab Shell Waste Chopper Technology. Additionally, it aims to transfer knowledge about the procedures for manufacturing, operating, and maintaining the Crab Shell Waste Chopper Technology in Puasana Village, North Moramo Sub-district, Konawe Selatan Regency. The method employed involves field visits, technical guidance, and the evaluation of activities conducted for the community. The results of the community service activity show that the community is well-informed and understands effectively the mechanisms for manufacturing, operating, and maintaining the crab shell waste chopper device used for livestock feed production. Furthermore, the evaluation provides a comprehensive understanding of the impact and sustainability of the crab shell waste chopper technology program in Puasana Village. These results can be used to enhance the program, ensure the continuity of innovation, and provide lessons for other areas interested in adopting a similar approach.